Food safety traits of mussels and clams: distribution of PCBs, PBDEs, OCPs, PAHs and PFASs in sample from different areas using HRMS-Orbitrap® and modified QuEChERS extraction followed by GC-MS/MS. Issue 5 (4th May 2018) - Chiesa, Luca Maria; Nobile, Maria; Malandra, Renato; Pessina, Davide; Panseri, Sara; Labella, Giuseppe Federico; Arioli, Francesco
ABSTRACT: Reviewing the presence of contaminant residues is important both for food safety and for monitoring of environmental pollution. Here, the occurrence of 6 polychlorinated biphenyls (PCBs), 15 organochlorine pesticides (OCPs), 7 polybrominated diphenyl ethers (PBDEs), 4 polycyclic aromatic hydrocarbons (PAHs) and 17 perfluoroalkyl substances (PFASs) was evaluated in mussels and clams. A liquid chromatography-high resolution mass spectrometry (HPLC-HRMS) and an innovative QuEChERS extraction followed by gas chromatography-tandem mass spectrometry (GC-MS/MS) methods were developed, validated and applied. We demonstrate good linearity, repeatability and accuracy of these methods, confirming that they are suitable for the analyses of mollusc samples. The prevalence of PCBs, OCPs and PAHs was higher in mussels than in clams. For PFASs, contamination was higher in clams than in mussels. The samples were all compliant with the regulations, and, for the compounds without legislative limits, a risk assessment confirmed that the values were lower than the tolerable intakes. GRAPHICAL ABSTRACT: